Algal flora of Rajarani Lake, Dhankuta and their seasonal distribution (Our Nature, 2017)
In this paper, a total 46 algae belonging to 34 genera and 3 classes (Chlorophyceae 54%, Bacillariophyceae 28%, Cyanophyceae 18%) have been reported from Rajarani Lake, Dhankuta, Nepal. Among these, 13 algae were reported as new to the country. Genera Ankistrodesmus, Closterium, and Desmodesmus had maximum number of species whereas 25 genera were represented by single species. Seasonal variation of algae showed that there was changing number and type of algae with physicochemical parameters in different seasons. Cyanophycean algae Microcystis flos-aque was dominant and observed in all sites in every collection of winter, summer and rainy seasons, and followed by bacillariophyceaean algae i.e., Aulacoseira granulata var. angustissima. The maximum number of algae was found in summer (59%) followed by winter (50%) and rainy (31%) seasons. There were 6 common algae found in all season’s viz. Ankistrodesmus falcatus, Aulacoseira granulata var. angustissima, Flagilaria tenera, Microcystis flos-aquae, Navicula radiosa and Oedogonium sp. Algae viz., Anabaena affinis, Cyclotella meneghiana, Pinnularia divergens, Pinnularia interrupta, Tetrastrum heteracanthum, and Ulothrix subtilissima were found only in winter season whereas, Aulacoseirsa granulata var. muzzanensis, Bolbochaete sp, Closterium striolatum, Cylindrospermum muscicola, Desmodesmus abundans, Desmodesmous quadricauda var.bicaudatus, Eunotia bilunaris, Gomphonema lacusrankaloides and Gomphonema pseudoaugur were observed only in summer. Similarly, Aphanocapsa pulchra, Oscillatoria sancta and Pediastrum duplex var. gracillimum were reported only in rainy season.